Penerapan Model Problem Based Learning Berbantuan Media Interaktif Wordwall Untuk Meningkatkan Hasil Belajar Peserta Didik - Siregar, Agnes M.; Sembiring, Metrilitna br; Pradesa, Dedi (Education Journal : Journal Educational Research and Development, 2024)
This Classroom Action Research (CAR) is based on the low learning outcomes in mathematics. The purpose of this CAR is to determine the improvement in learning outcomes in polynomial polynomial material. By implementing the Problem Based Learning Model with the help of interactive wordwall media, it can be a solution to improve student learning outcomes. This research is a classroom action research with the Kemmis and Taggart model research design and is carried out in two cycles. The research procedures used include planning, implementation, observation, and reflection. The research data were taken from the learning outcomes of class XI Biosfer students of SMA Negeri 2 Medan. The method used observation and tests Showing the percentage of completeness before and after the application of the approach, namely from 36.1% in the pre-cycle stage, increasing to 58% in cycle II. In addition, indicators of research success were also achieved, which included the average value of students reaching KKM. Increasing active participation of students, and achieving the percentage of completeness of students' mathematics learning outcomes of at least 75%.